DINAMIKA ISLAM PADA MASA ORDE BARU (1996-1998) - Afrita Rahma Amalia; Nisfia Rahma Nuril Izati; Mohammad Riski Arifin; Moh. Gilang Angga Kusuma; Muhammad Izzudin Al Wafa (UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
This study discusses the dynamics of Islam during the Orde Baru ‘New Order’ era from 1966–1998, especially the relationship between Islam, the military, and the state. The purpose of this study is to analyze the development of Islamic political movements, the military’s dominance in politics, and the accommodative policies of the New Order government toward Muslims. This research uses a literature study method by examining books, journals, and historical documents related to Islam and politics during the New Order period. The results show that at the beginning of the New Order, Islamic political movements experienced marginalization and strict political control through policies such as party simplification, the implementation of Pancasila as the sole ideology, and military domination through the ABRI dual-function doctrine. However, since the late 1980s, the relationship between Islam and the state gradually became more harmonious. The emergence of moderate Muslim intellectuals and the accommodative attitude of the government opened wider opportunities for Muslims in politics, bureaucracy, and social life. This condition marked the revival of Islamic politics in a more substantive and inclusive form. In conclusion, the dynamics of Islam during the New Order reflected a transition from political repression to accommodation between the state, military, and Islamic groups.